Styl internetowych ofert pracy w ujęciu kontrastywnym polsko-niemieckim - Szwed, Iwona (Stylistyka, 2019)
A starting point for this dissertation is an assumption that the cultural load should be considered a constitutive feature for differentiating between certain kinds of text (cf. Bilut-Homplewicz 2013: 145). Within the framework of contrastive research, covering the realization of various text models in different languages and cultural circles, the author of this article analyses online job advertisements, published on the Internet in German and Polish in 2014. These texts shall be considered autonomous in terms both the language used and cultural load, as created originally in the target language. Translated advertisements have been omitted, as potentially “contaminated” with the features of the source language. The author addresses the question of globalization (job market being highly globalized) and its possible influence on potential cross-linguistic and cross-cultural standardization within the notion of text genre. Contrastive analysis of job offers originating in different, yet relatively close cultural circles, allows for tracking current tendencies. These tendencies may be clearly visible in cases of international corporations, spreading its operations into various countries, which inevitably entails diffusing their corporate culture and standards, including their human resource know-how, in particular recruitment practices. The author also shares her reflections on the role of online job advertisements in the process of broadly understood corporate image building.